An uphill battle vs. a manageable situation: how do executive functions influence the association between obstacles and subjective well-being? - Lim, Benjamin Jun Gui (Nanyang Technological University, 2024)
The paths on which individuals tread towards their goals are often fraught with obstacles that serve to hinder the goal-pursuit process. These disruptions pose adverse effects on individuals’ subjective well-being (SWB), evoking negative affective states and potentiating negative self-evaluations. The processes that underlie how individuals cope with the onset of obstacles thus become of interest, as they could potentially alleviate the adverse impact of obstacles on individuals' SWB. Executive functions (EF) have been found to underlie the said self-regulatory mechanisms that are employed in the face of obstacles. As the ability to utilise these mechanisms effectively is related to the components of EF (i.e., inhibition, working memory, and cognitive flexibility), it is expected that EF could influence the association between obstacles and SWB. Through employing the Experience Sampling Method (ESM), we examined the effect of perceived obstacles on individuals’ SWB and investigated the moderating role of EF. As expected, results indicated a negative association between obstacles and SWB. While the said association persisted amongst individuals with lower levels of EF, the association did not reach statistical significance amongst individuals with higher levels of EF. This finding highlights the protective role of EF in mitigating the adverse effects of perceived obstacles on SWB. In the context of a nation with a vested interest in public health, the findings of the present study are valuable to boosting the overall well-being of communities.